(untitled) (Research, Society and Development, 2020)
This work aims to analyze the generation of biogas from anaerobic digestion in two stages in three batches. The work aimed at the comparative study of the anaerobic digestion of bovine manure (first batch) with the codigestion of bovine manure with whey diluted in whey in the proportion whey: bovine manure 15:60 (L: L) in the second batch and 5:60 (L: L) in the third batch, both having completed the rest with water. The biogas generated allowed the operation of an internal combustion engine. The anaerobic digester in two stages was designed to receive 60 liters of substrate in each stage, with hydraulic retention time of 45 days, 8% percentage of total solids, using an electronic temperature control system for 35ºC ± 5ºC and a mixer mechanical and two biogas purification biofilters to remove H2S and CO2. In each batch, before and after anaerobic digestion, a 1500mL content sample was collected for physical-chemical analysis of pH parameters, total, fixed and volatile solids, BOD, COD and Kjeldah total nitrogen. As qualitative results of biogas, from bovine manure substrate, the composition of 65% methane, 8% CO2 and 5% H2S was obtained in the first batch (only with bovine manure). With the substrate composed of bovine manure and whey, in the proportion of 5:60 (L: L) it led to better results with regard to pH (6.27) and Kjeldah total nitrogen (168mg / L).